Preparation and Characterization of TiO2/Expanded Graphite - 赖奇 朱世富 刘国钦 邹敏 李玉峰 罗学萍 (Transactions of Tianjin University, 2010)
In order to obtain anatase TiO2/expanded graphite with high expansion volume, titania gel was introduced to expandable graphite surface by sol-gel process, and then the composite was expanded and calcined at high tempera- ture. The samples were analysed by using scanning electron microscope （SEM）, X-ray diffraction（XRD）, energy disperse spectroscopy （EDS）, and differential scanning calorimetry （DSC）. The optimal conditions for preparation are as follows： the molar ratio of tetrabutyl orthotitanate to triethanolamine is 1 ： 0.4, and the calcination and expansion temperature is in the range of 650--750 ~C. Under such conditions, the expansion volume of composites could reach 98 mE/g, and the mass loss ratio is less than 5%. The analysis shows that lower temperature and smaller particle size of graphite are helpful to the formation of anatase-type of TiO2, but larger particle size will lead to lower mass loss ratio, and higher temperature and larger particle size will lead to higher expansion volume.